Sporotrichosis refractory to conventional treatment: therapeutic success with potassium iodide, - Lyra,Marcelo Rosandiski (2021)
Abstract Sporotrichosis is a subcutaneous mycosis caused by dimorphic fungi of the genus Sporothrix. The authors report a case of fixed cutaneous sporotrichosis with therapeutic failure after 18 months of itraconazole and terbinafine associated with cryosurgery. The patient was cured after the introduction of saturated potassium iodide solution. Sporothrix brasiliensis was the identified species, presenting a susceptibility profile to itraconazole and terbinafine. This fact suggests that therapeutic failure is probably related to the host-fungus interaction rather than drug resistance. It is possible that the immunomodulatory action of the saturated potassium iodide solution may have played an important role in curing this patient.